Assessment of Adequacy of Pain Management and Analgesic Use in Patients With Advanced Cancer Using the Brief Pain Inventory and Pain Management Index Calculation - Singh, Harminder (J Glob Oncol, 2016)
PURPOSE: The objective of this cross-sectional, noninterventional, 6-month observational study was to assess the adequacy of pain management in patients with cancer admitted to the Oncology Department of Guru Gobind Singh Medical College in Faridkot, India. METHODS AND MATERIALS: A total of 348 patients with cancer were recruited for evaluation of the prevalence of inadequate cancer pain management using the Brief Pain Inventory Pain Management Index. RESULTS: The current study included 127 males (36.5%) and 221 females (63.5%). The most prevalent cancer type was genitourinary; 268 patients (77%) had inadequately managed pain. A significant correlation was observed between poorly managed pain and age groups, analgesic used, and body mass index. CONCLUSION: Our observation of inadequate pain management among 77% of patients indicates that pain management was insufficient in three quarters of the patients in this study. Accumulating data regarding the inadequacy of cancer pain management is crucial to improve symptom management. Better management of pain not only alleviates pain symptoms but also increases the quality of life for patients with cancer.